2011
DOI: 10.1111/j.1600-0536.2011.01979.x
|View full text |Cite
|
Sign up to set email alerts
|

p‐Phenylenediamine and other hair dye sensitizers in Spain

Abstract: Hair dye substances categorized as potent skin sensitizers were used in all studied hair dye products on the Spanish market. The prevalence of p-phenylenediamine was higher in the present study than in a similar study in Sweden. More than 20 potent sensitizers were identified in each country. Not only p-phenylenediamine should be used to diagnose allergy to hair dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 14 publications
3
68
0
3
Order By: Relevance
“…Other health effects are more difficult to make a causal link with certain PCP ingredients. Therefore, most of the publications about negative effects of PCPs tend to focus on contact allergies, mainly caused by fragrances, dyes or preservatives, which skews the overall picture of related effects [22][23][24]. Studies sampling the general population with patch tests revealed that fragrance allergies to the standard set of fragrances (i.e., fragrance mix I) is an increasing clinical problem in many Northern and Southern hemisphere countries [25].…”
Section: Discussionmentioning
confidence: 99%
“…Other health effects are more difficult to make a causal link with certain PCP ingredients. Therefore, most of the publications about negative effects of PCPs tend to focus on contact allergies, mainly caused by fragrances, dyes or preservatives, which skews the overall picture of related effects [22][23][24]. Studies sampling the general population with patch tests revealed that fragrance allergies to the standard set of fragrances (i.e., fragrance mix I) is an increasing clinical problem in many Northern and Southern hemisphere countries [25].…”
Section: Discussionmentioning
confidence: 99%
“…All 105 oxidative hair dye products examined in a similar study conducted in Spain contained potent skin sensitizers (Table 1); 50% contained PPD and another 49% contained PTD or PTDS (10). In comparison, 16% of hair dyes sold in Sweden contained PPD and 80% contained PTD or PTDS (9).…”
Section: Hair Dyesmentioning
confidence: 99%
“…Hair dyes are composed of a variety of chemicals, including strong skin sensitizers such as p-phenylenediamine (PPD) and toluene-2,5-diamine (p-toluenediamine, PTD) (7)(8)(9)(10). Contact allergy to PPD is fairly frequent among dermatitis patients, and the prevalence seems to be higher in central and southern Europe than in northern Europe (11)(12)(13).…”
mentioning
confidence: 99%
“…The main worry is about the additives that may contain azo compounds and other amine, nitro, and other derivatives, which may be hazardous for the human health [49,[57][58][59]. As an example, in 1975, AMES et al [60] evaluated for the first time the mutagenicity of hair dye ingredients.…”
Section: Electroanalysis Of Hair Dyesmentioning
confidence: 99%